2020
DOI: 10.1038/s41598-020-78121-8
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase in the secretion of extracellular vesicles and antibiotics resistance from methicillin-resistant Staphylococcus aureus induced by ampicillin stress

Abstract: Extracellular vesicles (EVs) containing specific cargo molecules from the cell of origin are naturally secreted from bacteria. EVs play significant roles in protecting the bacterium, which can contribute to their survival in the presence of antibiotics. Herein, we isolated EVs from methicillin-resistant Staphylococcus aureus (MRSA) in an environment with or without stressor by adding ampicillin at a lower concentration than the minimum inhibitory concentration (MIC). We investigated whether EVs from MRSA under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Likewise, in another study, S. aureus had a significant increase in EVs release after exposure to the β-lactam antibiotics flucloxacillin and ceftaroline due to their ability to weaken the PGN wall [68]. Again, addition of the β-lactam ampicillin increased S. aureus EV production in a dose-dependent manner, which corresponded to a 22.4-fold increase at 64 μg/mL concentration [71]. The PGN present in the bacterial cell wall of most bacteria has a rigid structure formed of highly cross-linked polymers composed of polysaccharide chains and short peptides [81].…”
Section: S Aureus-evs Environmental Modulation 61 Impact Of Growth mentioning
confidence: 84%
See 2 more Smart Citations
“…Likewise, in another study, S. aureus had a significant increase in EVs release after exposure to the β-lactam antibiotics flucloxacillin and ceftaroline due to their ability to weaken the PGN wall [68]. Again, addition of the β-lactam ampicillin increased S. aureus EV production in a dose-dependent manner, which corresponded to a 22.4-fold increase at 64 μg/mL concentration [71]. The PGN present in the bacterial cell wall of most bacteria has a rigid structure formed of highly cross-linked polymers composed of polysaccharide chains and short peptides [81].…”
Section: S Aureus-evs Environmental Modulation 61 Impact Of Growth mentioning
confidence: 84%
“…Moreover, EVs derived from LB cultures were two-fold larger than those derived from BHI cultures, even though the latter presented higher protein diversity, which may also explain their significantly higher cytotoxicity towards neutrophils following brief exposure compared to LB-derived EVs [69]. In another study, proteomics identified 156 and 137 proteins in EVs derived from cultures in the presence and absence of a sub-inhibitory concentration of ampicillin, respectively, while only 67 proteins were shared by both conditions [71]. Another example of changes in EVs content was observed in the chemical composition of S. aureus EVs following treatment with vancomycin at 1 mg/ml.…”
Section: Impact Of Growth Conditions In S Aureus-ev Cargo Compositionmentioning
confidence: 98%
See 1 more Smart Citation
“…The penicillin‐binding proteins are involved in peptidoglycan synthesis and cell division (David et al ., 2018 ), but also offer binding sites to penicillin and β‐lactam antibiotics. This observation supports previous findings where EVs have been considered to contribute to bacterial survival by removing the antibiotics from the extracellular environment, acting as the decoy of antibiotic targeting or containing antibiotic‐degrading enzymes (Lee et al ., 2009 ; Chattopadhyay and Jaganandham, 2015 ; Kim et al ., 2018 ; Sabnis et al ., 2018 ; Bose et al ., 2020 ; Kim et al ., 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…MVs can stimulate biofilm formation, act as immunomodulators, increase bacterial resistance to host whole-blood killing, neutrophil killing, serum-complement killing, endogenous antimicrobial peptides and pharmaceutical antibiotics, and may in part be mediated by phenol-soluble modulins [10,11]. Previous studies suggest MVs confer certain SA protection against the lipopeptide membrane-active antibiotic daptomycin in vitro and ex vivo in whole blood, and that certain antimicrobial agents (e.g., gentamicin, cefotaxime, ampicillin and imipenem) can trigger bacterial MV release, potentially yielding antimicrobial resistance [12][13][14]. However, the role of methicillin-resistant Staphylococcus aureus-(MRSA) derived MVs and its implications in resistance to the first line therapeutic glycopeptide antibiotic vancomycin (VAN) has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%